Upgradation of conventional MBBR into Aerobic/Anoxic/Aerobic configuration: A case study of carbon and nitrogen removal based sewage treatment plant. (April 2021) - Osmani, Shakeel Ahmad; Rajpal, Ankur; Kazmi, A.A.
Graphical abstract: Highlights: Aerobic-Anoxic-Aerobic configuration system performed good potential in the nitrification process. The upgraded plant was examined by removing organic carbon and nitrogen through both PND and SND processes. Five hours HRT is enough for nitrogen removal, having a C/N ratio of more than four. PVA gel occupancy in MBBR achieved 50–90 % nitrification and >40 % denitrification in the form of SND. Both the geometry of carriers and the material used for carriers significantly influence the reactor's efficiency. Abstract: The thrust of this study was to assess the upgradation of an existing 3.5 million liters per day (MLD) full-scale conventional MBBR-based sewage treatment plant (STP) into Aerobic/Anoxic/Aerobic configuration. Initially, the plant was designed and constructed for achieving BOD and TSS to <30 mg/L and <50 mg/L, respectively. Recently, due to the advent of stringent effluent standards for BOD (Biological Oxygen Demand), TSS (Total Suspended Solids), and TN (Total Nitrogen) to <10 mg/L, with a strong emphasis on non-potable re-use of treated effluent, the existing system needed intensive upgradation. The upgraded STP was modified from two hours to five hours of hydraulic retention time (HRT). The upgraded plant was examined by removing organic carbon and nitrogen from municipal wastewater through both partial nitrification-denitrification (PND) by aerobic and anoxic reactors and simultaneous nitrification and denitrification (SND) process by PVA (Poly Vinyl Alcohol) gel aerobic reactor. After ten months of operation and monitoring, the plant has reached its upgraded effluent discharge standard. It was found that average BOD, COD, TSS, TN, and TP (Total Phosphorus) concentrations were 8 mg/L, 25 mg/L, 12 mg/L, 9 mg/L and 5 mg/L respectively, with 91 %, 90 %, 93 %, 84 %, and 64 %, removal efficiency. It was observed that PVA-gel beads are not only efficient for carbon removal (BOD & COD) but also achieve high SND rates.